2005
DOI: 10.1111/j.0269-8463.2005.00971.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed passage through birds and lizards on emergence rate of mediterranean species: differences between natural and controlled conditions

Abstract: Summary1. The ingestion of fruits by vertebrate frugivores produces great variation on seed germination responses which depend on (1) the frugivorous species; (2) several factors intrinsic to the plant species; and (3) the conditions under which germination tests are conducted. Most studies on this topic have used only one or a few disperser species, and have been performed under controlled conditions. 2. The main goals of this study were to determine (1) the effect that birds ( Turdus merula ) and lizards ( P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 36 publications
3
57
0
Order By: Relevance
“…and control (Valido, 1999;Nogales et al, 2005) all showed a similar percentage germination. An analogous result was also found by Rodríguez-Pérez et al (2005) for several Mediterranean plant species being dispersed by lizards and birds. Reanalysing their data, we found that seeds obtained from blackbird (Turdus merula) and Podarcis pityusensis (Lacertidae) droppings and controls resulted in a similar germination success for Rhamnus alaternus (Rhamnaceae), Rubia peregrina (Rubiaceae), Rubus ulmifolius (Rosaceae), Solanum luteum and Solanum nigrum (Solanaceae).…”
Section: Lizards As Seed Dispersers?supporting
confidence: 84%
See 1 more Smart Citation
“…and control (Valido, 1999;Nogales et al, 2005) all showed a similar percentage germination. An analogous result was also found by Rodríguez-Pérez et al (2005) for several Mediterranean plant species being dispersed by lizards and birds. Reanalysing their data, we found that seeds obtained from blackbird (Turdus merula) and Podarcis pityusensis (Lacertidae) droppings and controls resulted in a similar germination success for Rhamnus alaternus (Rhamnaceae), Rubia peregrina (Rubiaceae), Rubus ulmifolius (Rosaceae), Solanum luteum and Solanum nigrum (Solanaceae).…”
Section: Lizards As Seed Dispersers?supporting
confidence: 84%
“…Klein, 1977;Janzen, 1982;Iverson, 1985;Traveset, 1990;Hartley et al, 2000) and the omnivorous ones (e.g. Whitaker, 1987;Fialho, 1990;Valido and Nogales, 1994;Willson et al, 1996;Lord and Marshall, 2001;Olesen and Valido, 2003;Rodríguez-Pérez et al, 2005).…”
mentioning
confidence: 99%
“…Since the highest percentage of germination (14.5%) was recorded in the first year (compared to 2.8% in the second year and 0% in the third), we decided to carry out the remaining experiments for only 1 year. As reported by Rodríguez-Pérez et al (2005), seed emergence patterns in germination experiments can be contradictory in some cases when comparing field versus greenhouse-garden conditions. For this reason, to examine the quality of dispersal, two in situ germination experiments were also performed at both sites during the rainy period (November 2008-March 2009 in Riscos de La Fortaleza; October 2008-June 2009 in Malha Grande).…”
Section: Seed Proceduresmentioning
confidence: 90%
“…Rodriguez-Perez et al (2005) showed great heterogeneity in seed-emergence responses of different plant species to ingestion by different types of frugivores, and to different experimental conditions. In our experiments seed germination rates were accelerated in relation to control (seeds from the fruit) when passing through the gut of lizard and delayed when passing through the gut of eating-crab-fox.…”
Section: Discussionmentioning
confidence: 99%